Dynamic changes in clinical characteristics and serotype distribution of invasive pneumococcal disease among adults in Japan after introduction of the pediatric 13-valent pneumococcal conjugate vaccine in 2013–2019. Issue 24 (26th May 2022) - Tamura, Kosuke; Chang, Bin; Shimbashi, Reiko; Watanabe, Hiroshi; Tanabe, Yoshinari; Kuronuma, Koji; Oshima, Kengo; Maruyama, Takaya; Fujita, Jiro; Abe, Shuichi; Kasahara, Kei; Nishi, Junichiro; et al.
Highlights: Adult patients with IPD in Japan were analyzed by time periods in 2013 –2019. Serotype PCV13-nonPCV7 decreased in adult IPD patients after pediatric PCV13 use. Serotype PPSV23-nonPCV13 remained unchanged in those aged 15–64 y and ≥ 65 y. Nonvaccine serotypes increased in those aged ≥ 65 y, but not in those aged 15–64 y. 2018–2019 was independently associated with a lower risk of fatal outcome. Abstract: Nationwide population-based surveillance for invasive pneumococcal disease (IPD) is being conducted in few Asian countries. We aimed to evaluate the clinical characteristics and serotype distribution among Japanese adult patients with IPD after introduction of the pediatric 13-valent pneumococcal conjugate vaccine (PCV13) in 2013. IPD surveillance was conducted among adults between 2013 and 2019, and 1, 995 patients were analyzed by time period (early, 2013–2015; middle, 2016–2017; late, 2018–2019). We found that the period of 2018–2019 was independently associated with a lower risk of fatal outcome, compared with the period of 2013–2015. The proportion of those with serotype PCV13-nonPCV7 decreased significantly in patients aged 15–64 years and in those aged ≥ 65 years within 3 years after the introduction of pediatric PCV13. By contrast, the proportion of those with nonvaccine serotype increased significantly in those aged ≥ 65 years, but not in those aged 15–64 years. No significant change was found in the proportion of 23-valent polysaccharide pneumococcal vaccine (PPSV23)-nonPCV13 in both of adults aged 15–64 years and ≥ 65 years. The proportions of PCV15-, PCV20- and PCV24-covered serotypes were 38%, 56% and 58% in adult patients with IPD aged ≥ 65 years during the late period. Our data on the serotype distribution support an indirect effect from pediatric PCV13 use among adults, and afford a basis for estimates of protection against IPD by vaccination with newly developed PCVs in older adults in Japan.